Exorcizing the Landau ghost in noncommutative quantum field theory - Gurǎu, Rǎzvan (Journal of physics. Conference Series, 2008)
We show that the simplest noncommutative renormalizable field theory, the ø4 model on four dimensional Moyal space with harmonic potential is asymptotically safe to all orders in perturbation theory
Gesehen am 28.09.2022